INDUCED BANDGAP AND MAGNETIC BEHAVIOR IN ZIGZAG GRAPHENE NANORIBBONS ON HEXAGONAL NITRIDE BORON: EDGE AND SUBSTRATE EFFECTS - Viсtor Vasilyevich Ilyasov; Besarion Chokhoyevich Meskhi; Nguyen Van Chuong; Nguyen Duc Chien (Advanced Engineering Research, 2013)
The results of DFT research on the band structure of zigzag graphene nanoribbons N-ZGNR/h-BN(0001) with ferro- and antiferromagnetic ordering are presented. It is suitable as a potential base for new materials for spintronics. Equilibrium parameters of the graphene nanoribbon atomic structure and boron nitride top layer are determined as well as the equilibrium bond length   between atomic layers of the 8-ZGNR nanoribbon and the substrate h-BN(0001). Change regularities of the valence band electronic structure and of the energy gap induction in series 6-ZGNR→ 8-ZGNR→ 6-ZGNR/h-BN(0001)→ 8-ZGNR/h-BN(0001)→ graphene/h-BN(0001) are studied. Spin state features at Fermi level, as well as the roles of the edge effect and the effect of substrate in the formation of the band gap in 6(8)-ZGNR/h-BN(0001) system are discussed. It is shown that 340 meV energy gap appears in 6(8)-ZGNR/h-BN(0001) systems. The contribution of the graphene nanoribbon edge and substrate in opening this energy gap is differentiated. Local magnetic moments on the carbon atoms in graphene nanoribbons in the suspended state and on the substrate with ferro- and antiferromagnetic ordering are estimated. It is shown that the local magnetic moments on the carbon atoms in zigzag graphene nanoribbons 8-ZGNRs with ferro- and antiferromagnetic ordering give almost identical values. The edge carbon atoms possess the largest local magnetic moments (0,28) relative to other carbon atoms.